Stage makeup : the actor's complete step-by-step guide to today's techniques and materials - Thudium, Laura (Back Stage Books, 1999)
"Whether you are an actor in a summer-stock or regional theater, an acting conservatory program, a high-school or college production, a community theater, a local holiday pageant...or anywhere else, this is the best all-purpose "how-to" guide to makeup for the theater." "Besides period makeup, age makeup, and special-effects applications, the book delves into fantasy makeup, animal faces, and other kinds of stylization found on the contemporary stageand with the use of the most up-to-date materials." "Explaining all the basic techniques the actor needs, the author offers tips on putting together a personal makeup kit, analyzing one's own facial features, creating a picture file, caring for one's skin, and using a color-mixing chart." "Here, then, is the most complete makeup resource - for students, for amateur groups, for everyone performing on today's stage, and at any level." --Book Jacket.